Controle de acesso para laboratório - Tori, Renan Lorenzi (2014)
This assignment shows the design and construction of a prototype of an access controller, that will be used in a laboratory of the Federal Technological University of Parana campus Toledo, which goal is to allow the access to the laboratory for people authorized. The controller was designed using the development board STM32VLDISCOVERY from ST that has a microcontroller ARM Cortex-M3, which contain all the requirements needed for the construction of the prototype. The system has a barcode reader, numeric keypads, flash memory, a LCD display and one eletromechanical lock triggered from a voltage inverter. Additionally, the system is battery operated to be unaffected by power outage.